Analysis of differential item functioning in agricultural science examination across southwestern nigeria's senior schools - Opesemowo, Oluwaseyi Aina Gbolade; Babatimihin, Temitope; Ogungbaigbe, Temitope Sarah (Jurnal Bidang Pendidikan Dasar, 2024)
Differential Item Functioning poses a threat to test fairness and validity in educational assessments. To this end, this study probes the incidence of DIF in the Senior School Certificate Agricultural Science Examination (SSCASE) across school locations in Southwestern Nigeria. It determined the magnitude of DIF using item parameters in SSCASE. The study applies one, two and three-parameter logistic models to analyze the dichotomous data responses of 818 randomly selected students from urban and rural locations. The ex-post facto design adopted the 2015 National Examination Council SSCE in Agricultural Science as its instrument (Î± =0.887) in this study. The study population comprised SSCE candidates from Osun, Ondo, and Oyo. The results showed the magnitude of DIF in SSCASE was large and moderate (1PLM=0.52 significant DIF, 2PLM=0.45 moderate DIF, 3PLM=0.47 moderate DIF) across school locations. The study concluded that 1, 2 and 3 PLMs can produce fair items in SSCASE.